Representation of Omitted Variable Bias with the Total Derivative Method (Contemporary Mathematics, 2024)
This study aims to provide an understanding of the concept of omitted variable bias through the total derivative method. This novel approach that is often overlooked could bring a new perspective to statisticians, econometricians, or researchers in neighboring disciplines such as social sciences, management, or economics. In order to complement this mathematical method, the study also employs graphical representations. By doing so, we provide a detailed walkthrough of the total derivative method, its visual depiction, and its application to the omitted variable bias. We believe that this approach can enhance the understanding of regression analysis and foster a deeper connection between mathematics and econometrics. Overall, this study can contribute to the development of new theoretical foundations using the total differential method in this context.
Keywords: omitted variable bias; total differential; total derivative; multivariate regression